Self-management and self-efficacy of women with gestational diabetes mellitus: a systematic review. Issue 1 (31st December 2022) - Karavasileiadou, Savvato; Almegwely, Wafa; Alanazi, Anwar; Alyami, Hanan; Chatzimichailidou, Sofia
ABSTRACT: Background: Gestational diabetes mellitus (GDM) is a temporary form of diabetes induced by pregnancy and is potentially harmful to both the mother and fetus The impact of GDM diagnosis on pregnant women needs to be taken into account. This is related to the capacity for self-management of GDM, for which quality evidence is still lacking. Objective: to identify several aspects of self-management and self- efficacy for women with GDM. Method: Electronic databases were searched for studies related to the self-management, self-efficacy, and glycemic control of women with GDM, from January 2012 to January 2021. The extraction of study features was based on study location, reported research aims, study design, methodology, and the analytical approach, using Endnote Version X7.7.1. The Critical Appraisal Skills Program Qualitative Checklist (CASP) was used to assess quality, as recommended by the Cochrane Qualitative Research Methods Group. Results: Ten out of 70 studies were identified as meeting the established criteria and including a diverse population. The synthesis revealed seven major themes: preliminary psychological impact, communicating the diagnosis, knowledge of GDM, self-efficacy and self-management of GDM, risk perception, the burden of GDM, and gaining control. The benefits of a diagnosis were behavioral and were mostly crystalized if a particular level of self-management and self-efficacy was reached and women were able to have specific control over their diet and body weight. On the other hand, women reported that the diagnosis increased their responsibility, as they had to take extra precautions regarding their dietary regimen. Conclusion: Self-management and self-efficacy for GDM management are possible, despite the psychological hurdles that most women confront. There is still potential for improvement in terms of developing a healthy lifestyle that not only manages GDM for the best pregnancy result, but also prevents diabetes after pregnancy.